Outcomes of total hip replacement in adults with septic arthritis of the native hip joint: A systematic review - Teddy Cheong; Surya Varma Selvakumar; Ryan Kwang Jin Goh; Ing How Moo (Arthroplasty)
Abstract Background Septic arthritis is a debilitating condition that results in joint destruction and irreversible loss of joint function. Surgical treatment options include arthroscopy, resection arthroplasty, and total hip replacement (THR). Current literature on the treatment of septic arthritis of various joints includes periprosthetic or native joints. However, to our knowledge, a consolidated review that focuses solely on THR outcomes in a previously infected native hip is still lacking. This systematic review, for the first time, examined the clinical outcomes of THR, specifically in adults with septic arthritis of the native hip joint. Methods PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), SCOPUS, Cochrane Library, grey literature, and bibliographic references were searched from inception to October 2023. Only case series or cohort studies published within the last 20 years assessing the outcomes of THR for native hip septic arthritis were included. Literature retrieval and data extraction were conducted by three independent reviewers. Re-infection rate and various functional outcomes, measured in terms of the Harris Hip Score (HHS), Visual Analogue Scale (VAS), Merle D'Aubigne and Postel (MAP), Western Ontario, McMaster Universities Arthritis Index (WOMAC) Short Form 12-Item (SF-12) scores, were analyzed. Range of motion (ROM) and limb length discrepancy (LLD) were also examined. Results Against the relevant criteria, seven studies (six case series, one cohort study) involving 1243 patients were included. The patients aged from 18 to 78 years old. The reinfection rate ranged from 0 to 22.8%, with a mean rate of 19.6%. With regards to functional outcomes, the mean increase in HHS was from 39.5 to 48.92 and the increase in MAP ranged from 7.3 to 10.9. Improvement in LLD ranged from 2.28 to 3.52 cm, with all studies reporting < 1 cm of LLD postoperatively. Conclusion THR, both single and two-staged, is an effective treatment option for septic arthritis of the native hip joint that and yields good functional outcomes and acceptable reinfection rates. However, more prospective and randomized trials are needed to establish clear protocols on antibiotic regimes, clinical criteria clearance, and optimal time from infection to joint replacement.